On, With, By?Advancing Transgender Health Research and Clinical Practice (Mary Ann Liebert, 2023)
To advance the fields of transgender health research and clinical care and center trans-led scholarship, there must be an acknowledgment of the consolidated power in cisgender hands and the subsequent need to redistribute such power to trans experts and burgeoning trans leaders. To redress the social structures that cause harm and limit opportunities for trans persons to lead, current cisgender leaders can take actions including deferring opportunities to trans persons to ensure a redistribution of power and resources to trans experts. This article presents necessary steps to recruit, collaborate, and elevate trans experts.